ANALISA DAMPAK KETERLAMBATAN AIRLINES OPERATOR DALAM MENGIRIM SLOT DELAY TERHADAP PELAYANAN LALU LINTAS UDARA DI PERUM LPPNPI CABANG AMBON - Vanny Yulviani; Ade Irfansyah; Paramita Dwi Nastiti (Prosiding SNITP (Seminar Nasional Inovasi Teknologi Penerbangan))
This Final Project describes the obstacles faced by the author regarding the analysis of the impact of delays in Airlanes Operator sending Slot Delay on air traffic services at Perum LPPNPI Ambon Branch. The emergence of these obstacles is due to the frequent delays of Airlines Operators in sending information regarding changes to slot delays so that the slot delay management process carried out by ACO personnel serving in the ARO Unit will be hampered, the ARO Unit must send a delay message 15 minutes before the EOBT time. The purpose of writing this final project is to facilitate ACO personnel in performing ATS Messages services so as not to interfere with flight safety services. The data analysis method is descriptive quantitative. This research uses data processing in the form of a Likert scale which refers to sources that are relevant and have credibility. The results of this study are expected to provide alternative problem solving so that ACO personnel can provide maximum service